NEW PUBLIC MANAGEMENT DAN MILLENIUM DEVELOPMENT GOALS SEBUAH CARA UNTUK MENGATASI MASALAH DI NEGARA BERKEMBANG - Sapto Pramono (Universitas Tribhuwana Tunggadewi, 2014)
Poverty is complex because it involves many aspects of public policy that is not exactly right for the fulfillment of food, health, education, employment, and so on. In order to decrease poverty in Indonesia may need the support and cooperation of the community and the government's seriousness in tackling this problem. Through the Millennium Development Goals (MDGs), the government tried to reduce poverty, it's just that certain requirements must be met. In this case the requirement is about the readiness of the government in implementing the MDGs, because the government should be in a position of good governance in accordance with the development paradigm of the New Public Management (NPM). Theoretical understanding of public policy dominated NPM shift to governance and public policy (public services) to market-oriented citizens. So that the public policy and public service with NPM paradigm is the issue of public sector and participation, as the empowerment and participation of the public sector is expected to be cooperation between the government and citizens without being harmed.